Perizinan Sempadan Sungai Terhadap Usaha Rumah Makan Terapung - Khalik, Widya Dwi Erika Idham; Saleng, Abrar; A.Sapiddin, Andi Syahwiah (Universitas Widya Gama Malang, 2023)
This study aims to analyze the arrangements related to the utilization of the river riparian which is used as a restaurant business in the Tello Baru Sub-District, Makassar City and to analyze the form of government supervision of the implementation of river riparian utilization permits in the Tello Baru Sub-District, Makassar City. This research is an empirical research, where the data is qualified as primary and secondary data. Primary data was obtained through interviews, and secondary data was obtained through literature studies. The data collected is then processed using a qualitative analysis approach.The results of the study show that the utilization of river banks which are used as a restaurant business in Tello Baru Village, Makassar City is not in accordance with the Decree of the Minister of PUPR Number 1559/KPTS/M/2020 which states that river banks can only be used for certain activities and certain buildings, which include: Buildings natural resources infrastructure, bridge and wharf facilities, gas and drinking water pipelines, electrical and telecommunication cable stretches, other activities as long as they do not interfere with the function of the river, including activities to plant vegetables, and electricity buildings. So that the use of the Tello River opportunity for floating restaurant activities can be said to not realize orderly spatial planning. And then the form of government supervision of the implementation of river riparian utilization permits in Tello Baru Village, Makassar City is felt to be lacking, in this case the Pompengan Jeneberang River Basin Center (BBWS) as the vanguard of the Ministry of PUPR as the guardian of Law No. 17 of 2019 concerning Water Resources is considered to be still not active in monitoring the abuse of the Tello River border area resulting in violations of the use of the river border. as it is now. The Pompengan Jeneberang River Basin Center (BBWS) is considered to be lacking in coordination and cooperation with the City Government and Village Governments through which the Tello River passes.